Dyslipidemia among Patients with End Stage Renal Disease on Maintenance Hemodialysis - Mohammed Ghazi Abdulhadi; Mohammed Omer Mohammed; Fenk Bakir Maarouf (Kurdistan Journal of Applied Research, 2018)
Dyslipidemia has been suggested to be one of the factors that contribute to the high incidence of cardiovascular disease in hemodialysis patients. Previous studies suggest that end-stage renal disease may contribute to dyslipidemia. The aim of the study: to assess the prevalence of dyslipidemia in patients on maintenance hemodialysis. Patients and Methods: A case-control study was conducted from February 2015 until August 2015 in Ibn-Sena teaching hospital on 100 participants (52 males and 48 females), 50 were patients with end-stage renal disease on regular hemodialysis and 50 were age and gender-matched apparently healthy subjects as the control. Questioner used to collect data, a thorough examination was done including height and weight and BMI. A blood sample from all participants in fasting state was sent for the renal function test, complete blood picture, serum albumin, electrolytes, TG, total cholesterol, LDL and HDL measured by the enzymatic method, plasma atherogenic index calculated as [log (TG/HDL)].   Results: Age of the participants ranged between 18 - 70 years and the mean age was (44.45 ± 13.6) years. In HD group, the mean cholesterol  was  (3.29 + 0.73) mmol/l, serum TG (2.38 ± 0.56) mmol/l, LDL (1.91 ± 0.66) mmol/l, HDL (0.88 ± 0.2) mmol/l, atherogenic index (0.434 ± 0.16), while in control group, the mean cholesterol  was (4.17 ± 0.69) mmol/l, serum TG (1.6 ± 0.43) mmol/l, LDL (2.69 ± 0.63 ) mmol/l, HDL (1.066 ± 0.13) mmol/l, atherogenic index (0.177 ± 0.12).  The lipid abnormalities in hemodialysis group were high plasma atherogenic index in 84%, hypertriglyceridemia 50%, hypercholesterolemia 8% and high LDL  6% and low HDL in 48%, while in control group, high plasma atherogenic index in 34%, hypertriglyceridemia in 26%, hypercholesterolemia 14% high LDL 7% and low HDL in 16%. Conclusions: patients with end-stage renal disease on hemodialysis have significant dyslipidemia compared to control group characterized by hypertriglyceridemia, low HDL and high atherogenic index of plasma.